2012
DOI: 10.1103/physreva.86.033424
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the generation of high-order harmonics through Bohmian trajectories

Abstract: We theoretically investigated the generation progress of high-order harmonics utilizing Bohmian trajectories, which are calculated from the accurate numerical wave function. It is found that the harmonic emission spectrum from atoms in an intense laser field calculated by Bohmian trajectories agrees well with that found by numerically solving the time-dependent Schrödinger equation. Through the analysis of the dynamic behavior of Bohmian trajectories, we investigated the ionization process, the acceleration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 19 publications
3
30
0
2
Order By: Relevance
“…The harmonic generation spectrum can be calculated from the Fourier transform of the electric dipole induced in an atom inside an oscillating field, which corresponds to the mean position of the electron inside a hydrogen atom. It has been shown that trajectories from different parts of the electron wave packet contribute to different parts of the harmonic spectrum [89]. On the one hand, those trajectories starting far from the nucleus which ionize and oscillate with the field frequency provide a better representation of the low-frequency part of the spectrum.…”
Section: Intense Light-matter Interactionmentioning
confidence: 99%
“…The harmonic generation spectrum can be calculated from the Fourier transform of the electric dipole induced in an atom inside an oscillating field, which corresponds to the mean position of the electron inside a hydrogen atom. It has been shown that trajectories from different parts of the electron wave packet contribute to different parts of the harmonic spectrum [89]. On the one hand, those trajectories starting far from the nucleus which ionize and oscillate with the field frequency provide a better representation of the low-frequency part of the spectrum.…”
Section: Intense Light-matter Interactionmentioning
confidence: 99%
“…The calculation of the quantum potential or guiding waves requires the knowledge of the N -electron wave function, thus we need some approximation. It is not obvious how to systematically improve such approximation, although Bohmian trajectories extracted from the wave function calculated with other methods give some insights into strong-field phenomena [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The followed question will be when and how the electron is diffracted to construct rings either in spatial or momentum distribution. To see that, we showed some typical Bohmian trajectories [26][27][28][29] in Fig. 3 (c).…”
Section: Simulation Resultsmentioning
confidence: 96%